Formulation of smokeless tobacco products with a wide range of pH to study nicotine pharmacokinetics and pharmacodynamics. (3rd July 2022) - Hoag, Stephen W.; Mishina, Elena V.; Viray, Lauren; Wang, Fang; Hollenbeck, Gary; Koszowski, Bartosz; Pickworth, Wallace B.
Abstract: The rate of nicotine absorption from tobacco products is a determinant of addiction potential and other detrimental health effects. Oral nicotine bioavailability from moist snuff smokeless tobacco (ST) is influenced by nicotine content, pH, flavors, and tobacco cut. For use in a clinical study testing the effect of pH on nicotine pharmacokinetics, four investigational ST products that differed only in pH were produced. A commercial ST product (Copenhagen Long Cut Original, pH 7.7) was modified with citric acid monohydrate (23 mg/g tobacco) or sodium carbonate (4.6 and 11 mg/g) to create products with pH 5.0, 8.2, and 8.6, respectively. All products – including the original product with pH 7.7 – were individually packaged (approximately 2 g) in aluminum foil pouches and stored frozen (−20 °C); pH, nicotine, tobacco-specific nitrosamines, moisture content, and mold and yeast counts were tested for up to 19 months to verify stability. Remarkable stability was demonstrated in this packaging/storage combination. For example, pH from all products were within 0.1 pH units and never exceeded 0.2 units. Nicotine concentration averaged 9.07 mg/g at baseline, maximal deviations from baseline in the four products averaged 0.30 mg/g. Similarly, TSNA, moisture content, yeast, and mold did not materially change. This study illustrates a method of investigational tobacco products formulation by manipulating a single design feature (or component) with the purpose of independently and systematically assessing its influence on nicotine bioavailability in a clinical study.